2003
DOI: 10.1002/hed.10276
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy for angiosarcoma

Abstract: Only the location of the primary tumor was a predictor of local control and absolute survival at 5 years. Angiosarcomas located on the scalp imply a dismal prognosis compared with those in other locations with the predominant pattern of failure being local recurrence. Patients should be treated aggressively with surgical resection and preoperative or postoperative radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
60
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 22 publications
4
60
2
2
Order By: Relevance
“…Four patients also received chemotherapy, mainly with docetaxel. This treatment achieved a better local control rate (86% at 3 years) than previous studies ( Figure 3) (3,8,11,12,(18)(19)(20)(21)(22). The primary tumors of two patients who had presented with invasion of the skull and temporal muscle and received a total dose of 70 Gy in 35 fractions progressed after radiation therapy.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Four patients also received chemotherapy, mainly with docetaxel. This treatment achieved a better local control rate (86% at 3 years) than previous studies ( Figure 3) (3,8,11,12,(18)(19)(20)(21)(22). The primary tumors of two patients who had presented with invasion of the skull and temporal muscle and received a total dose of 70 Gy in 35 fractions progressed after radiation therapy.…”
mentioning
confidence: 64%
“…Although previous studies have presented the outcomes of radiation therapy for angiosarcoma of the scalp, all of these series involved more than a few patients with tumors in other primary sites, including the face, body trunk, and extremities, and/or who had undergone surgery prior to radiation therapy (3,8,9,11,12,(21)(22)(23). Therefore, it is very difficult to determine the true efficacy of definitive radiation therapy for angiosarcoma of the scalp.…”
mentioning
confidence: 99%
“…Because both surgery and radiotherapy have been reported to be effective treatments for local therapy [6,7], we compared the LC rates according to the treatment modality and total radiation dose. Table 4 shows the LC status of radiotherapy with or without surgery according to total radiation dose.…”
Section: Recurrence Patternsmentioning
confidence: 99%
“…Since several reports have provided proof of a treatment efficacy of radiotherapy and surgery for patients with angiosarcoma of the scalp and face, this treatment combination has been recommended as an ideal treatment of these tumours [1,6,7,14]. Guadagnolo et al [14] analysed 70 patients with angiosarcoma of the scalp and face and found that combined surgery and radiotherapy was associated with improved OS, diseasespecific survival and LC compared with surgery or radiotherapy alone.…”
Section: Angiosarcoma Of the Scalp And Facementioning
confidence: 99%
See 1 more Smart Citation